Aortic Graft Infection: Graphene Shows the Way to an Infection-Resistant Vascular Graft - Patelis, Nikolaos; Schizas, Dimitrios; Liakakos, Theodoros; Klonaris, Chris (Frontiers in Surgery, 2017)
Aortic graft infection is a potentially lethal complication of open and endovascular repair of aortic aneurysms. Graphene is the only existing two-dimensional material and its unique structure gives graphene and its derivatives a plethora of original characteristics. Amongst other characteristics, graphene demonstrate bacteriostatic and bactericidal effects that could potentially resolve the problem of graft infection in the future. Data already exist in literature supporting this antibacterial effect of graphene oxide (GO) and reduced graphene oxide (rGO). Combining these materials with other substances enhances the antibacterial effect. Additionally, it looks feasible to expect antibiotic-delivering graphene-based graft materials in the future. Based on already published data, we could conclude that regarding graphene and its derivatives, the blessing of bactericidal effect comes with the curse of human cells toxicity. Therefore, it is important to find a fine balance between the desired antibacterial and the adverse cytotoxic effect before graphene is used in graft materials for humans.